Comparison of the Outcome of Drain Vs Pressure Dressing in Ventral Hernia Repair - Faridoon, Shehla; Shah, Muhammad; Iftikhar, Muhammad; Ahmad, Siddique; Aslam, Rashid; Hadi, Ainul; Alam, Muhammad (Journal of Gandhara Medical and Dental Science, 2021)
OBJECTIVES: The purpose of this study was to compare the outcome of drain vs. pressure in ventral hernia repair. METHODOLOGY: A cross sectional comparative study conducted at the Department of General Surgery, Hayat Abad Medical Complex Peshawar from January 2018 till December 2019. One twenty six patients both male and female were admitted as elective cases through OPD and were divided into “A” and “B” groups. Experienced surgeons of the unit performed all surgeries. Postoperative pain, seroma/hematoma formation, wound infection and hospital stay was noted in both groups. RESULTS: Out of 126 patients, 32 (25.3%) were males while 94 (74.6%) were females with male to female ratio of 1:3. All types of hernia were more common in the age range of 31-50 years. The common complications in both groups were seroma/hematoma formation (7.1%) and wound infection (6.3%). Mean hospital stay was 2-4 days. CONCLUSION: Mesh repair is the standard procedure for ventral hernia repair. Postoperative complications are comparatively lesser in pressure dressing than those with drain placement group.